Analisis Perlakuan Akuntansi Warkat Kliring Tertolak dan Dampaknya terhadap Laporan Keuangan Bank - Joy Eklesya Silaban; Dean Christian Hutajulu; Romanty Julia Hutasoit; Willy Sangga Reja Galingging; Thalia Sreshi Oxana Sidabalok; Hamonangan Siallagan (Lembaga Pengembangan Kinerja Dosen, 2026)
Rejected clearing instruments are one of the operational risks frequently encountered by banking institutions and may affect the reliability of financial statements if they are not accounted for properly. The accounting treatment of rejected clearing instruments includes recognition, measurement, recording, and presentation that must comply with applicable financial accounting standards and banking regulations. This research aims to analyze the accounting treatment of rejected clearing instruments and its impact on bank financial statements, particularly on earnings quality, asset valuation, and credit risk. The research method employs a qualitative approach using literature review and descriptive analysis of accounting practices in the Indonesian banking sector. Data are obtained from academic journals, financial accounting standards, and regulations related to clearing systems and financial instruments. The results indicate that improper accounting treatment of rejected clearing instruments may lead to misstatements in receivable accounts, revenue recognition, and allowance for impairment losses, which ultimately affect the fairness of financial statements. Therefore, banks are required to implement consistent accounting policies in accordance with prevailing standards to enhance transparency, accuracy, and the reliability of financial information presented to stakeholders.